2017
DOI: 10.1038/srep41555
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of acute kidney injury after orthotopic liver transplantation in China

Abstract: In this study, we determined the risk factors for acute kidney injury (AKI) following orthotopic liver transplantation (OLT) in China. We collected 5074 donation after cardiac death (DCD) OLT recipients who underwent surgery between January 1, 2010, and December 31, 2015, in 86 academic hospitals or transplant centers in China. Univariate and multivariate analyses were used to investigate the criticality of donor, graft, or recipient variables in the development of post-OLT AKI. In all, 4482 patients were incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
58
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 59 publications
4
58
1
Order By: Relevance
“…Zongyi et al . [ 26 ] concluded that the elevation of preoperative Cr (>353.6 μmol/L [40 mg/L]) was an independent risk factor for post-OLT AKI.…”
Section: Discussionmentioning
confidence: 99%
“…Zongyi et al . [ 26 ] concluded that the elevation of preoperative Cr (>353.6 μmol/L [40 mg/L]) was an independent risk factor for post-OLT AKI.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the study subjects are diverse in this setting. Among patients who develop AKI after OLT, approximately 8-17% need renal replacement therapy (RRT) [2]. AKI after OLT was associated with immediate complications including volume overload, metabolic acidosis, and electrolyte disturbances [3] and an increased rate of inferior long-term outcomes such as mortality, graft loss, infection, chronic kidney disease, prolonged stay in the intensive care unit (ICU), and augmented hospital costs [1,4].…”
Section: Introductionmentioning
confidence: 99%
“…A wide variety of mechanisms have been reported for the development of AKI after OLT, such as female gender, pre-existing diabetes mellitus (DM) [5], the severity of liver disease [6], preoperative renal dysfunction [7][8][9], perioperative events especially hepatic ischaemia reperfusion injury (IRI) [10,11], toxicity of immunosuppressive therapy [2,12,13], and other miscellaneous etiologies. As the etiology of AKI after OLT are multifactorial and not well understood, timely preventive therapy or medical interventions performed during the initiation phase of AKI can minimize the extent of injury and promote renal recovery, therefore the cornerstone for reducing the development of AKI after OLT is early recognition of high-risk patients alongside active perioperative management.…”
Section: Introductionmentioning
confidence: 99%
“…Despite decades of investigation, mitigation of transplant immune rejection with less severe complications remains a challenge. Traditional clinical anti-rejection drugs, such as cyclosporin A and tacrolimus, comprehensively inhibit T cell activity by mainly binding to calcineurin of the cells and suppressing IL-2 release, which leads to numerous severe adverse effects [ 53 ]. Thus, it is important to find new drugs that can be specifically directed against specific T sub-populations on anti-transplanted rejection and result in less adverse effects [ 3 ].…”
Section: Discussionmentioning
confidence: 99%